2012
DOI: 10.1177/0022034512456551
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Their Target Genes in Gingival Tissues

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. AbstrActTo gain insights into the in vivo function of miRNAs in the context of periodontitis, we examined the occurrence of miRNAs in healthy and diseased gingival tissues and validated their in silico-predicted targets through mRNA profiling using whole-genome microarrays in the same specimens. Eighty-six individuals with periodontitis contributed 198 gingival papillae: 158 'diseased' (bleeding-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
196
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(208 citation statements)
references
References 40 publications
(53 reference statements)
12
196
0
Order By: Relevance
“…Surprisingly, these three reports yielded completely different results, probably because of differences in ethnicity and experimental conditions. However, hsa-miR-223 was overexpressed in inflamed gingiva in both this study and the American study (12). miR-223 is involved in many types of cancer, inflammatory diseases, autoimmune diseases, and in pathological processes such as leukemia, RA, and cardiovascular disease (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Surprisingly, these three reports yielded completely different results, probably because of differences in ethnicity and experimental conditions. However, hsa-miR-223 was overexpressed in inflamed gingiva in both this study and the American study (12). miR-223 is involved in many types of cancer, inflammatory diseases, autoimmune diseases, and in pathological processes such as leukemia, RA, and cardiovascular disease (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 45%
“…A study of Americans found 25 miRNAs that were upregulated (>2.63-to 1.48-fold) in inflamed gingiva. The three most overexpressed miRNAs were hsa-miR-451, hsa-miR-223, and hsa-miR-486-5p (12). Surprisingly, these three reports yielded completely different results, probably because of differences in ethnicity and experimental conditions.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Other than the global intervention of microRNA machinery, miR-155 (65), miR146a (66), and miR-223 (28,67) were identified to be related with osteoclastogenesis. miRNAs were identified in periodontitis gingiva as well (68). Nevertheless, a lack of systemic analysis of microRNAs involvement in apical periodontitis is obvious.…”
Section: Discussionmentioning
confidence: 99%